A 12‐Week, Prospective, Non‐Comparative, Non‐Randomized Study of Magnetic Muscle Stimulation for Improvement of Body Satisfaction With the Abdomen and Buttocks. Issue 1 (8th November 2020) - Fabi, Sabrina; Dover, Jeffrey S.; Tanzi, Elizabeth; Bowes, Leyda E.; Tsai Fu, Felicia; Odusan, Abi
Abstract : Background and Objective: Magnetic muscle stimulation (MMS) is a relatively new energy‐based technology that provides a non‐invasive option for body contouring through stimulation and toning of underlying skeletal muscles. This study was conducted to examine the safety, efficacy, and body satisfaction scores of MMS using a CoolToneTM prototype for the aesthetic improvement of abdominal and buttock contour. Study Design/Materials and Methods: This was a prospective, non‐comparative, non‐randomized, 12‐week, multicenter study. Male and female participants aged 22‐65 years received 4 MMS treatment sessions to the abdomen and/or buttocks. Body Satisfaction Questionnaire (BSQ) scores for abdomen and/or buttocks were assessed at baseline, immediately post final treatment, at 4 weeks (primary endpoint), and 12 weeks post final treatment. Subject‐rated Global Aesthetic Improvement Scale (SGAIS) was assessed at 4 weeks post final treatment (secondary endpoint), and 12 weeks post final treatment. Additional efficacy assessment included abdominal circumference obtained by 3D imaging at baseline, immediately post final treatment, and at 4 and 12 weeks post final treatment. A Subject Experience Questionnaire (SEQ) was used to assess treatment satisfaction and perspectives at 4 weeks and 12 weeks post final treatment. Adverse events (AEs) were monitored throughout the study. Results: A total of 110 participants were recruited, who were 75% female, 80% Caucasian (mostly non‐Hispanic), average age of 39.5 years (range 22–59) with an average body mass index (BMI) of 23.3 kg/m2 (range 18–29.9). At the 4‐week post final treatment visit, the average BSQ score for participants receiving abdominal treatment (n = 93) was significantly improved with a 5.1 average increase in total score from baseline (possible score range 10–50) and by a 5.5 average increase from baseline for participants receiving buttocks treatment (n = 32) (p < 0.05). At 4 weeks post final treatment, the proportion of participants with SGAIS scores >"Improved" was 68.1% for participants receiving treatment of the abdomen (n = 94), and 81.8% for those receiving buttocks treatment (n = 33). The mean total decrease from baseline in waist circumference was significant at all time points. At the 12‐week post final treatment visit, SEQ data revealed that a majority of participants were "Satisfied" or "Very Satisfied" with overall treatment results and "Agreed" or "Strongly Agreed" that they were motivated to maintain results either by working out or by additional treatment. A total of 6 AEs related to the device and/or treatment were reported, which resolved spontaneously during the study. Conclusion: Treatment of the abdomen and/or buttocks with MMS was well‐tolerated and demonstrated significant improvement in aesthetic appearance through the 12‐week post final treatment study duration. As a stand‐alone treatment, MMS expands the range of options for individualized treatment planning for patients seeking abdominal and/or gluteal muscle toning. © 2020 The Authors. Lasers in Surgery and Medicine published by Wiley Periodicals, Inc.